PERUBAHAN RERATA SKOR NYERI PUNGGUNG PADA IBU HAMIL TRIMESTER III SEBELUM DAN SESUDAH DIBERIKAN MASSAGE EFFLEURAGE - Tri Nanda Sukma Nur Fatimah; Ima Syamrotul Muflihah (VISIKES: Jurnal Kesehatan Masyarakat, 2022)
Background: pregnant women will lose their balance and they will tend to stretch their back and neck which may cause their lower backbend and their lower back muscles pulled which may inflict pain. Massase therapy is oneof the non-pharmacological therapies that can reduce back pain for pregnant women, massage will reducemuscle tension and pain, increase mobility and improve blood circulation. Purpose: To find out the changes in the mean score of back pain in the third trimester of Pregnant Women before and effleurage massage inWanatawang Village, Songgom Sub-district, Brebes Regency. Method: This was pre-experimental research withone group pretest-posttest design with 25 pregnant women as the respondents. The inclusion are : pregnant women who have back pain. The data were collected using a questionnaire and analyzed using Wilcoxon signed-rank test. Results: The mean score before being given effleurage massage was 6.75 andchanged to 3.56 after being given the massage with a scale of 3.91 and a p-value of 0.0000 (<0.05). The analysis results showed that there was a change of mean score before and after effleurage massage. Conclusion: effleurage massage was effective on the change of mean score of back pain in the third-trimesterpregnant women.Keywords: Effleurage Massage, Back Pain, Third Trimester Pregnant Women